(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article examines the complex leadership dynamics between Enver Pasha (Anvar Posho) and indigenous Central Asian warlords during the Basmachi resistance movement in Turkestan from 1921 to 1922. Through comprehensive analysis of historical sources and scholarly literature, the study investigates the ideological conflicts, strategic disagreements, and power struggles that characterized the relationship between the Ottoman military leader and local commanders, particularly Ibrahim Bek. These internal divisions significantly weakened the Basmachi forces and contributed to their eventual defeat by the Red Army.